Biologic Joint Repair Strategies: The Mizzou BioJoint Story. (October 2017) - Kuroki, Keiichi; Stoker, Aaron M.; Stannard, James P.; Bozynski, Chantelle C.; Cook, Cristi R.; Pfeiffer, Ferris M.; Cook, James L.
Because articular cartilage has very limited healing potential, most symptomatic cartilage injuries eventually result in end-stage osteoarthritis and are treated with artificial joint replacement. Our interdisciplinary, comparative orthopedic research performed by a team of DVMs, MDs, engineers, and basic scientists has yielded marked progress toward effective biologic joint restoration strategies by bringing bench-side ideas to fruition in bedside applications in both canine and human patients. This mini-review summarizes the progress of biologic joint restoration strategies at our center.